FAKTOR-FAKTOR YANG MEMPENGARUHI TRANSPARANSI PEMERINTAH (WILAYAH PROVINSI DI PULAU JAWA) - Rizky Novananda Fauzan Hasibuan; Dul Muid (Diponegoro Journal of Accounting, 2022)
The purpose of this study is to determine the factor that influence the level of transparency of local government through empirical testing, particularly financial reports is the most important part that must be submitted by the Regional Government since regional autonomy was implemented by the Central Government. This study was conducted in 6 provinces on the island of Java in 2013-2018. Sampling is done using the purposive sampling method Hypothesis testing used significance test and multiple linear regression analysis. The data collection method is obtained the local government website. The results of hypothesis testing in this study indicate that the presentation of regional financial reports has a significant positive effect on the use of regional financial information by information users.